DEVELOPMENT OF HOTS-BASED TEACHING MATERIALS TO IMPROVE STUDENTS' PROBLEM-SOLVING SKILLS IN ISLAMIC RELIGIOUS SUBJECTS AT SD MUHAMMADIYAH 18 PALEMBANG - Apriansyah, Andika; Harto, Kasinyo; oviyanti, Fitri (Jurnal Asy-Syukriyyah, 2025)
The low use of teaching materials that stimulate higher-order thinking skills, while students at the concrete operational stage according to Piaget already have the potential to be trained in logical and analytical thinking. This study aims to develop HOTS-based teaching materials to improve the problem-solving skills of fourth-grade students at SD Muhammadiyah 18 Palembang. This research uses the Research and Development (R&D) method with the Planning, Production, and Evaluation (PPE) model, involving observations, interviews, questionnaires, and pre-and post-tests to measure the effectiveness of the product. The validation results show that the developed teaching materials fall into the high category in terms of content and design, with consistent reliability testing. The paired sample t-test shows significant improvement in students' problem-solving skills after using HOTS-based teaching materials (t value = -10.791; sig. 0.000), compared to the control group (t value = -3.994; sig. 0.000), and the independent sample t-test strengthens the significant difference between groups (t value = 3.875; sig. 0.000). Thus, the HOTS-based teaching materials are proven to be valid, effective, and can serve as an innovative model in the development of Islamic Religious Education learning in elementary schools.